2013
DOI: 10.1155/2013/160162
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Concrete Bricks with Recycled Expanded Polystyrene Aggregate

Abstract: Cellular concrete bricks were obtained by using a lightweight mortar with recycled expanded polystyrene aggregate instead of sandy materials. After determining the block properties (absorption, compressive strength, and tensile stresses), it was found that this brick meets the requirements of the masonry standards used in Mexico. The obtained material is lighter than the commercial ones, which facilitates their rapid elaboration, quality control, and transportation. It is less permeable, which helps prevent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This implies that applying thermal treatment on polystyrene foam particles helped in enhancing their strength. The results showed that MEPS aggregate in (FCM25) helped in increasing the compressive strength by about 68% of that of conventional foamed concrete (FC12 mix), see Figure 4b, noted that a similar behaviour was noticed by Hernández et al [20]. It was found that the crashing load of MEPS aggregate particle was higher than that of expanded aggregate particle (EPS) by about 20 times, which results in gaining compressive strength for mixes containing MEPS higher than that of EPS mixes.…”
Section: Compressive Strengthsupporting
confidence: 76%
“…This implies that applying thermal treatment on polystyrene foam particles helped in enhancing their strength. The results showed that MEPS aggregate in (FCM25) helped in increasing the compressive strength by about 68% of that of conventional foamed concrete (FC12 mix), see Figure 4b, noted that a similar behaviour was noticed by Hernández et al [20]. It was found that the crashing load of MEPS aggregate particle was higher than that of expanded aggregate particle (EPS) by about 20 times, which results in gaining compressive strength for mixes containing MEPS higher than that of EPS mixes.…”
Section: Compressive Strengthsupporting
confidence: 76%
“…In terms of reuse, bricks obtained by recycled XPS aggregate, instead of mineral sands, obtained good performances (Bosco Hernández-Zaragoza et al., 2013), and a permeability coefficient decrease with the increase in consolidation pressures and curing age (Zhu and Ma, 2015).…”
Section: Main Textmentioning
confidence: 99%
“…Aerated concretes are a variation within lightweight concretes that have a specific mass between 320-1920 kg/m 3 and a compressive strength above 1.5 MPa [24]. Lightweight concretes can be obtained by the use of lightweight aggregates in the mixture or by the incorporation/production of air in the form of bubbles distributed into the mortar [25,26]. The lightweight concretes known as autoclaved aerated concrete (AAC) are those that are produced with bubbles of air inside the mortar via a chemical reaction process activated by curing in an autoclave [27].…”
Section: Introductionmentioning
confidence: 99%